Coronary revascularization and sex differences in cardiovascular mortality after myocardial infarction in 12 high and middle-income European countries - Cenko, Edina; Yoon, Jinsung; Bergami, Maria; Gale, Chris P; Vasiljevic, Zorana; Vavlukis, Marija; Kedev, Sasko; Miličić, Davor; Dorobantu, Maria; Badimon, Lina; Manfrini, Olivia; Bugiardini, Raffaele (Oxford University Press (OUP), 2024)
Existing data on female sex and excess cardiovascular mortality after myocardial infarction (MI) mostly come from high-income countries (HICs). This study aimed to investigate how sex disparities in treatments and outcomes vary across countries with different income levels.
Keywords: Myocardial infarction; Outcomes; Sex differences; middle-income countries